Iris zhaoana, a new name for Iris potaninii var. ionantha (I. sect. Pseudoregelia ser. Tigridiae, Iridaceae) from China: evidence from morphological and plastid DNA data - Crespo, Manuel B.; Alexeeva, Nina B.; Xiao, Yue E. (Phytotaxa, 2020)
The new name Iris zhaoana is proposed to replace I. potaninii var. ionantha, which is applied to a dwarf bearded iris described from western China, usually included in I. sect. Psammiris. It is a plant occurring at high elevation and showing roots thick and grey; leaves glaucous-green, blunt to subacute and shortly mucronate at apex; flower solitary, dichromic, bluish-violet, with standards and falls similar in shape and size; falls more richly blotched with deep-violet and with whitish areas; beard of white and blue-white hairs, tipped yellow; fruits globose-ovoid to ellipsoid, shortly acuminate at apex; and seed with a comparatively prominent, large, yellow aril. These features closely relate I. zhaoana to members of I. sect. Pseudoregelia, namely to I. tigridia, with which it has sometimes been confused. Morphological and molecular data are discussed here that support recognition of the Central Asian plant at species rank and its inclusion in I. sect. Pseudoregelia ser. Tigridiae.